If it's not what You are looking for type in the equation solver your own equation and let us solve it.
63-2x=79-3x
We move all terms to the left:
63-2x-(79-3x)=0
We add all the numbers together, and all the variables
-2x-(-3x+79)+63=0
We get rid of parentheses
-2x+3x-79+63=0
We add all the numbers together, and all the variables
x-16=0
We move all terms containing x to the left, all other terms to the right
x=16
| Z+8z=9 | | x-x(.10)=56772 | | -5+4n+n=-40+5n | | -4x+30=23(x+33) | | 4x-2+2(5x+3)=-4(x+1) | | 2/5(n)=12 | | -3=x-5/6 | | 4p+3=3(p-2) | | -3/4x+1/4=13/4 | | -7g-5=8+3g-2 | | 1/3.x=20 | | -4w-11=18 | | 3x+5x+4-x+8=88 | | 3(w-3)-4=-2(-8w+2)-7w | | x-8/11=-2 | | 2(6x-8)=40+4x | | -5+4n+n=2n+15 | | -9=3w+4(w+3) | | -5g(-1)(8-g)=12 | | 7q-9=40 | | 18=5u+2(u-5) | | -61-15x=1-20x+38 | | 5x+8+3x+4=-40+ | | 39=6v+3(v+4) | | 6x-17=3x+40 | | 4=-2r | | 39=6v+3(v=4) | | 5x-2(x-5)=-8+5x+10 | | -14x+132=26(x-18) | | x^2-29x+154=0 | | 6x17=3x+40 | | 0.5(4x-8)+3x=36 |